Facilitators and barriers in interprofessional collaboration around physical activity on prescription-a focus group study in a Swedish school setting - Emelie Wiklund; Jenny Vikman; Maria Wiklund; Susanna Hedenborg (Frontiers Media S.A., 2024)
In Swedish school health services, local initiatives have been taken to use physical activity on prescription (PAP) to encourage physically inactive children to become more active. Previous research shows that interprofessional collaboration plays a crucial role in promoting physical activity in children, as well as in promoting health in schools. However, there is a lack of knowledge about PAP for children in the school setting, including how medical and educational staff can work together to encourage children who have been recommended PAP. Therefore, this study aims to explore the perceived facilitators and barriers concerning interprofessional collaboration regarding physical activity on prescription in the school setting, as viewed from the professionals' perspectives. Semi-structured interviews were conducted with 21 professionals who work with the method in school settings. The data were analyzed using Reflexive Thematic Analysis. The results reveal both barriers and facilitators for interprofessional collaboration on PAP in the school setting, as perceived by professionals. Organizational and structural obstacles within school institutions hinder collaboration, while a shared commitment to PAP, characterized by consensus-building, acts as a facilitating factor. PAP for children in a school setting is still an unexplored area and further research is required.